Pemodelan kapabilitas organisasi terhadap kinerja ditinjau dari faktor kepemimpinan-budaya organisasi-perilaku politik dalam organisasi- studi kasus pada kelompok perkebunan kelapa sawit negara dan kelompok perkebunan kelapa sawit swasta - Bangun, Yuni Ros; Mangkuprawira, Sjafri; Saefuddin, Asep; Djohar, Setiadi (Jurnal Manajemen Teknologi, 2010)
Organizational Capability is considered to be one of the most important issues in strategic management and human capital literature. Organizational Capability can be understood as the all elements that work efficiently and effectively to help organization create its strategy that fits to its industry level of turbulence and to achieve company performance.  Previous research  confirmed the identification  of nine (9) elements as organizational capability. These are speed innovation, customer connectivity, seeks related change,  strategic  responsiveness,  international working  environment,  ready  to  strategic  alliances, efficiency  and  talent. Research  confirmed  that Organizational Capabilities  have  positive  impact  to Organizational Performance. Research shows the connection between the three variables –Leadership –Organizational Culture and Political Behavior in creating Organizational Capability and its impact to Organizational Performance. Structural Equation modeling shows that Leadership and Organizational Culture do not have direct relationship with Organizational Performance, however both have positive relationship  with  Organizational  Capability.  Organizational  Performance  was  directly  influenced positively by Organizational Capability and negatively impacted by Organizational Politics. Leadership positively impact Organizational Capability and Organizational Culture, however leadership negatively impact Organizational Politics.Keywords: Strategic Management,Organizational Capability,Strategic Leadership, Culture,Organizatinal Politics,Government Owned Companies